Improving Students’ Reading Comprehension of Expository Text through A-C-T-I-V-E Technique at SMP Negeri 1 Pematangsiantar - Dewi Paulina Silalahi (Universitas Pahlawan Tuanku Tambusai, 2023)
Reading comprehension is a necessary skill throughout schooling and a vital component of the successful transition to adult responsibilities. A-C-T-I-V-E is strategies that specifically support students’ comprehension of factual text and goals to improve teaching of reading in the classroom. The purpose of the study is to find out whether the students’ comprehension in reading expository text improved if it is taught by using A-C-T-I-V-E technique. Classroom action research was conducted in this study. The result of research indicated that there was improvement on the students’ reading comprehension which was taught by A-C-T-I-V-E technique. It was proved by the data which showed that the mean of the students in the second cycle, 79.06, was higher than in the first cycle, 67.34 and also in the pre-test 49. The quantitative data were taken from test a pre-test and two tests in post test in cycle I and post test in cycle II. The qualitative data were taken from diary notes, interview sheet, observation sheet and questionnaire sheet also showed that the students’ interest in reading comprehension increased because they could share their knowledge and their opinion each other and also find the definition of difficult words together. Keywords: Reading comprehension, expository text, a-c-t-i-v-e technique. Abstrak Pemahaman membaca adalah keterampilan yang diperlukan selama sekolah dan komponen penting dari transisi yang sukses ke tanggung jawab orang dewasa. A-C-T-I-V-E adalah strategi yang secara khusus mendukung pemahaman siswa tentang teks faktual dan tujuan untuk meningkatkan pengajaran membaca di kelas. Tujuan dari penelitian ini adalah untuk mengetahui apakah pemahaman siswa dalam membaca teks ekspositori meningkat jika diajar dengan menggunakan teknik A-C-T-I-V-E. Penelitian tindakan kelas dilakukan dalam penelitian ini. Hasil penelitian menunjukkan bahwa terdapat peningkatan pemahaman membaca siswa yang diajar dengan teknik A-C-T-I-V-E. Hal ini dibuktikan dengan data yang menunjukkan bahwa rata-rata siswa pada siklus II 79,06 lebih tinggi dibandingkan siklus I yaitu 67,34 dan juga pada pre-test 49. Data kuantitatif diambil dari tes satu pre-test dan dua tes pada post-test pada siklus I dan post-test pada siklus II. Data kualitatif yang diambil dari catatan harian, lembar wawancara, lembar observasi dan lembar angket juga menunjukkan bahwa minat siswa dalam membaca pemahaman meningkat karena mereka dapat berbagi pengetahuan dan pendapat mereka satu sama lain dan juga menemukan definisi kata-kata sulit secara bersama-sama. Kata kunci: Pemahaman membaca, teks ekspositori, teknik a-c-t-i-v-e.